“Doing the courses without stopping my life”: Time in a professional Master’s program - Oliphant, Tami; Branch-Mueller, Jennifer (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
This study investigates how time intersects with student learning in Canada’s first, and only, Master of Library and Information Studies (MLIS) in an online teaching and learning stream.  Thirty-two students responded to a survey that asked about their experiences, perceptions, and challenges after their first year of the program.  Descriptive statistics and NVIVO 10 were used to analyze survey responses and to develop themes through open coding.  The findings indicate that time shapes students’ decisions to pursue the MLIS online, their perception of what the degree might mean for their future, their experience in the program, the quality of their relationships, and their learning.  The perceived flexibility of the MLIS program was incredibly important to students.  However, the majority of students described themselves as “time poor” and many students underestimated the time commitment necessary to complete the program, to manage coursework, and to build and maintain relationships with others.